Histometric analysis of ligature-induced periodontitis in rats: a comparison of histological section planes - Delle Vedove Semenoff, Tereza Aparecida [UNESP]; Semenoff-Segundo, Alex; Bosco, Álvaro Francisco [UNESP]; Nagata, Maria José Hitomi [UNESP]; Garcia, Valdir Gouveia [UNESP]; Biasoli, Eder Ricardo [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2008)
The purpose of this study was to analyze the histometry of ligature-induced periodontitis in rats at different histological section depths. Sixteen male adult Wistar rats were randomly assigned to two groups: ligature and control. In the ligature group, rats received a sterile 4/0 silk ligature around the maxillary right 2nd molar. Thirty serial sections containing the 1st and 2nd molars, in which the coronal and root pulp, cementoenamel junction (CEJ) in the mesial side of the 2nd molar, interproximal alveolar bone and connective fiber attachment were clearly visible, were selected for histometric analysis. The histological sections were clustered in groups of 10 sections corresponding the buccal (B), central (C) and lingual (L) regions of the of periodontal tissue samples. The distance between the CEJ in the mesial side of the 2nd molar and the attached periodontal ligament fibers (CEJ-PL) as well as the distance between the CEJ and the alveolar bone crest (CEJ-BC) were determined. From CEJ-PL and CEJ-BC distances measured for each specimen, the measurements obtained in the B, L and C regions were recorded individually and together. Data were submitted to statistical analysis. Significant differences (p<0.001) were observed between the control and ligature groups regarding CEJ-PL (0.05 mm and 0.26 mm, respectively) and CEJ-BC (0.47 mm and 0.77 mm, respectively) measurements. Regarding the depth of the buccal, central and lingual planes, the means of CEJ-PL and CEJ-BC of both groups showed no statistically significant differences (p>0.05). In conclusion, the selection of 10 serial sections of the central region of periodontal tissue samples at any depth can be considered as representative for the evaluation of periodontal ligament fiber attachment and bone loss in ligature-induced periodontitis in rats.
Keywords: experimental periodontitis; methodology; periodontal diseases; rats